[About CEU - Part 9]
The continuation of the series “About CEU” and the second part of the video about the CEU Conference and Residence Center. The reporter is interviewing students in the computer labs or in their rooms. The discussions revolve around the living conditions in the dormitory, the facilities offered by the university and the usual activities in the dorm. Images from the Gym inside the building and the indoor court where students can practice basketball, badminton, volleyball, soccer and tennis are also presented in this video. The recording ends with images from the cafeteria.